Gender-Based Violence Awareness Assessment Tool for Children with Intellectual Disabilities in Special Schools - Yayu Khoerul Bariyyah; Oom Sitti Homdijah; Endang Rochyadi (Mimbar Ilmu, 2025)
The background of this study on children diagnosed with intellectual disabilities (ID) shows an increased vulnerability to gender-based violence (GBV) due to their cognitive, communicative, and social vulnerabilities. This study aims to present the development and psychometric evaluation of a GBV awareness instrument, consisting of 25 items designed for students with mild to moderate intellectual disabilities in Special Schools (SLB) in Indonesia. The items cover four main domains: recognition of physical restraint, identification of violence scenarios, avoidance and reporting strategies, and safe behavior practices. The research design uses instruments informed by Piaget's cognitive development theory, Bandura's social learning theory, and UNESCO's Comprehensive Sexuality Education guidelines. The results of the study show that the item content validity index (I-CVI) ranges from 0.80 to 0.95 and the cumulative validity index (s-CVI/AVE) is 0.88. A pilot study involving 20 students (aged 10 to 15 years; consisting of 10 boys and 10 girls) from SLB Angkasa, Bandung, confirmed the applicability of the instrument. The internal consistency of the instrument was considered acceptable (Cronbach's α = 0.82). A comparison of pre- and post-tests after a brief school-based attention intervention revealed a statistically significant increase in all domains (total pre-test score M = 13.4, SD = 2.7; post-test M = 19.6, SD = 2.1; p <0.01), indicating a moderate to large effect size. In conclusion, this instrument demonstrates practicality for teacher-administered screening and program evaluation in the context of SLB.